Experimental investigations into the influence of AlSi-10Mg soft tool coating on the machinability of Ti6Al4V. Issue 12 (10th September 2022) - George, Allan; Kuriachen, Basil; Dhanish, P.B.; Mathew, Jose
ABSTRACT: Machinability of Grade 5 titanium alloy, despite its extensive usage in fields of aerospace and biomedical applications, is extremely challenging as a result of various features like its poor thermal conductivity, chemical reactivity, work hardening nature, etc. Although various methodologies and coating techniques have developed over the years, a significant improvement in its machinability characteristics is yet to be achieved. This study is an effort to analyze the effect of AlSi-10 Mg soft coating developed by pre-conditioning technique on tool life and surface integrity characteristics and to compare the observed results with that of the uncoated insert in the dry cutting process. It was seen that AlSi-10 Mg coating developed over the cutting edges helped in minimizing the effects of adhesion and diffusion wear along the tool faces due to its self-lubricating properties and cushioning effect that it provided at the cutting interface, thereby contributing to encouraging results in tool life improvement in contrast to the unprotected uncoated insert. Moreover, favorable chip morphology and better surface finish were generated when machined using AlSi-10 Mg soft coated inserts.